Controlling biofilms on cultural materials: the role of 3-(dodecane-1-thiyl)-4-(hydroxymethyl)-2, 2, 5, 5-tetramethyl-1-pyrrolinoxyl. Issue 16 (26th January 2015) - Alexander, Stefanie-Ann; Rouse, Emma M.; White, Jonathan M.; Tse, Nicole; Kyi, Caroline; Schiesser, Carl H.
Abstract : 3-(Dodecanethiyl)-4-(hydroxymethyl)-2, 2, 5, 5-tetramethyl-1-pyrrolinoxyl (5 ) effectively disperses biofilms of relevance to cultural materials while preventing their formation. Abstract : 3-(Dodecanethiyl)-4-(hydroxymethyl)-2, 2, 5, 5-tetramethyl-1-pyrrolinoxyl (5 ) effectively disperses biofilms of relevance to cultural materials while preventing their formation.